Financial Analysis and Marketing of Sugar Palm (Arenga pinnata) Fruit at Simantin Village, SubDistrict of Pematang Sidamanik, District of Simalungun - Astri Winda Siregar; Agus Purwoko; Tri Martial (Peronema Forestry Science Journal, 2013)
Sugar palm (Arenga pinnata) is a plant that almost all its parts can be utilized. One of the products is sugar palm fruit that are processed into kolang-kaling. Today, information of kolang-kaling economic value is limitted, so that people were uninterested in process it. Therefore, this research aims to analyze the financial analysis and marketing of sugar palm fruit. The research had done in Desa Simantin, Kecamatan Pematang Sidamanik, Kabupaten Simalungun. Respondents of this research were the business actors of processing sugar palm fruit into kolang-kaling and the business actors of selling kolang-kaling. The method of data analysis were financial analysis and marketing analysis. The results showed that the processing of kolang-kaling business worth the effort because the value of R/C ratio was more than 1 that is 2,75 with number of BEP volume production was 272,33 kg, number of BEP price was IDR 909,54 and the duration payback period was after 2 times production. Flow of kolang-kaling marketing started from processors, collectors, retailers, and up to consumers. The marketing margin was IDR 3500,00 with share of profit (Ski) of collector area equal to 28.57% and share of profit (Ski) of retailers equal to 71.43%. Keywords: sugar palm fruit, financial analysis, marketing margin, kolang-kaling